N-[2-(4-Bromobenzoyl)ethyl]isopropylaminium chloride - Abdullah Aydın; Mehmet Akkurt; Halise Inci Gul; Ebru Mete; Ertan Sahin (Acta Crystallographica Section E, 2012)
The crystal structure of the title compound, C12H17BrNO+·Cl−, is stabilized by N—H...Cl and C—H...O hydrogen bonds, forming a three-dimensional network. The interactions framework is completed by C—H...π contacts between a methylene group and the benzene ring of a symmetry-related molecule.